Engineering transferrable microvascular meshes for subcutaneous islet transplantation - Wei Song (Nature Portfolio, 2019)
The success of engineered tissue depends on the integration of a dense vascular network to supply nutrients and remove waste products. Here the authors design high density microvascular meshes made through an anchored self-assembly mechanism, and use these meshes to support subcutaneous pancreatic islet survival in a mouse diabetes model.